Deviasi Kata dan Perubahan Makna Bahasa pada Sosial Media Facebook - Mulasih Mulasih; Yukhsan Wakhyudi (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
The purpose of this study is first, to describe the word deviation contained in the various languages ​​of social media Facebook. Second, describe changes in meaning in the various languages ​​of Facebook social media. This research is a qualitative descriptive study for two reasons. First, the problems to be examined, carefully observed are described later concluded. This study aims to make a description, description, painting systematically, factually, and accurately regarding the data, the characteristics and relationships of the phenomena studied. Second, this study includes deskiptif qualitative research, namely research carried out by describing or describing and describing the data then continued by analyzing word deviation, word deviation process and its use on Facebook. The results of this study are language deviations which are prevalent and are rapidly developing among teenage facebookers. Although this language, it is not in the spelling that is perfected in Indonesian (PUEBI), but they freely use this language in their own world. The word deviation occurs a lot from the aspect of reduction and addition to the original word, so that the new words formed do not exist in Indonesian. The word formation is excessive and contains changes in meaning associations that contain humor.